A QUANTITATIVE APPROACH TO AQUIFER VULNERABILITY MAPPING - Connell L.D.; Daele G.V.D. (My University, 2003)
This paper presents a procedure for calculating the transport to groundwater of surface-released contaminants. The approach is derived from a series of analytical and semi-analytical solutions to the advection-dispersion equation that include root zone and unsaturated water movement effects on the transport process. The steady-state form of these equations provides an efficient means of calculating the maximum concentration at the watertable and therefore has potential for use in vulnerability mapping. A two-layer approach is used in the solutions to represent the unsaturated profile, with the root zone corresponding to the upper layer where evapotranspiration can occur and transport properties can be in contrast to the rest of the profile. A novel transformation is applied to the advection-dispersion equation that considerably simplifies the way in which water movement is represented. To provide a combined flow and transport model an approximate procedure for water movement, using averages of the infiltration and transpiration rates with a novel, simple, quasi-steady state solution, is presented that can be used in conjunction with the solutions to the advection-dispersion equation. This quasi-steady state approximation for water movement allows for layering in the soil profile and root water uptake. Results from the combined quasi-steady state water movement and semi-analytical solute transport procedure compare well with numerical solutions to the coupled unsaturated flow and solute transport equations in a series of hypothetical simulations.
Keywords: VULNERABILITY MAPPING; UNSATURATED SOLUTE TRANSPORT; ADVECTION-DISPERSION EQUATION; ANALYTICAL SOLUTIONS